The Financial Performance of Family versus Non-Family Firms Operating in Nautical Tourism - Santos, Eleonora (2022)
This article analyses the financial performance of family versus non-family firms operating in nautical tourism, in 2015–2019. The sample of 39 Portuguese companies was collected from the SABI database. We use a regression of financial performance, measured by three alternative proxies: return on assets, return on equity and operating profit margin, on liquidity, leverage, turnover of assets, asset structure, company size and age. The regressions are performed across Nuts II regions on mainland and across types of firms (family and non-family). The results uncover several patterns. First, family firms are larger and older, make higher investments and therefore are less liquid. Second, liquidity, leverage and investment in tangible assets impact negatively and significantly the corporate financial performance, while the turnover of assets, size and age impacts positively and significantly. Third, the sign of the impacts depends on the measure of performance. Finally, firms in the Northern region show superior performance, which can be explained by the higher share of family firms. These findings can serve as a roadmap for managers when selecting strategies to improve performance. Additionally, they will contribute to the understanding of tourism destination dynamics and competitiveness.